The use of GIS in the study of forms and methods of water erosion in the Great Atlas of the Middle - Arif, Said; boazza, salak; El-Khalki, Yahia; Bourkiba, Ahmed Amine (Journal of natural sciences, life and applied sciences, 2019)
The morphogenesis or water erosion is a phenomenon that shows the link between the dynamics of erosion and the natural factors that control its intensity. Indeed, the watershed of Oued El Abid upstream of the dam bin al ouidane is an important area for the study of the current forms of erosion of which we find different forms.This study aimed to treat current forms of erosion to determine their proportions and geographic distributions. We concluded that this region included a variety of different forms (9 forms) due to erosion in the area and the diversity of its slopes and rocks; as well as the density of vegetation that contributed to morphogenesisIn addition, the objective of this study is to interpret aerial photographs and satellite images and to map erosion patterns as well as to validate the results on the Oued El Abid watershed.Indeed, the study found that the area of areolaire erosion accounted for 50% of the total area of the basin, while the gutter erosion account for only 7%. Landslide erosion extends over 10%; rockslide of 9% and Bad-Lands accounted for 6%.The study recommended the need to intervene to reduce the intensity and spread of water erosion through a comprehensive approach that takes into account the activities of civil society and accumulated scientific research to reduce the deterioration of the natural environment.
Keywords: water erosion forms; geographic information systems; Aley Bain El Ouidan Dam; Wadi El Obeid Basin; Aley Umm Ar-Rabi